ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR PINANG (ARECA CATECHU) DI PROVINSI JAMBI - Ismadinata, Febrian; Napitupulu, Dompak; Damayanti, Yusma (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
This study was aimed to analyze the factors that affect the export of arecanut (Areca catechu) in Jambi Province, and to forcast the development of areca nut export value from Jambi Province in for 10 years. The data used were secondary data obtained from related institutions. This research was carried for January 2018 to February 2018. Doubled linear regression analysis was a tool that used in analyzed factors affecting areca nut export from Jambi, and to forcast the development of export value 10 years ahead was used a trend method. Regression results show that the factors that affect the export of areca nut from Jambi Province were areca nut production, local areca nut price, areca nut export value, rupiah exchange rate against US dollar, and export volume of previous year. The result of the analysis also showed that the variables affecting the export were the previous year's export volume variables which significantly influence, and the forecasting result for the export volume of Areca catechu 10 years ahead using quadratic trend method with model Ŷt 7387330,422 – 310082,759t + 4936,4640t2was the best model. Forecasting result showed an increase in the year 2026 was 112.985.848 Kg. Keywords: Export, Export Factor, Forecasting, Trend Analysis.